Evaluation of the 2‐(1‐Hexyloxyethyl)‐2‐devinyl pyropheophorbide (HPPH) mediated photodynamic therapy by macroscopic singlet oxygen modeling. Issue 11 (22nd September 2016) - Penjweini, Rozhin; Kim, Michele M.; Liu, Baochang; Zhu, Timothy C.
Abstract : Photodynamic therapy (PDT) is known as a non‐invasive treatment modality that is based on photochemical reactions between oxygen, photosensitizer, and a special wavelength of light. However, a dosimetric predictor for PDT outcome is still elusive because current dosimetric quantities do not account for the differences in the PDT oxygen consumption rate for different fluence rates. In this study, we evaluate several dose metrics, total fluence, photobleaching ratio, PDT dose, and mean reacted singlet oxygen (mean [ 1 O2 ]rx ) for predicting the PDT outcome and a clinically relevant tumor re‐growth endpoint. For this reason, radiation‐induced fibrosarcoma (RIF) mice tumors are treated with 2‐(1‐Hexyloxyethyl)‐2‐devinyl pyropheophorbide (HPPH) and different in‐air fluences (30 J/cm 2, 50 J/cm 2, 135 J/cm 2, 250 J/cm 2, and 350 J/cm 2 ) and in‐air fluence rates (20, 50, 75, 150 mW/cm 2 ). Explicit measurements of HPPH and oxygen concentration as well as tissue optical properties are performed pre‐ and post‐treatment. Then, this information is incorporated into a macroscopic model to calculate the photobleaching, PDT dose, and mean [ 1 O2 ]rx . Changes in tumor volume are tracked following the treatment and compared with the dose metrics. The correlation demonstrates that mean [ 1 O2 ]rx serves as a better dosimetric quantity for predicting treatment outcome and a clinically relevant tumor re‐growth endpoint. Abstract : Concentration of the reacted singlet oxygen ([ 1 O2 ]rx ) can be calculated using singlet oxygen explicit dosimetry of light fluence (rate), initial tissue oxygenation, and photosensitizer concentration using a macroscopic model for HPPH‐mediated photodynamic therapy (PDT) in radiation‐induced fibrosarcoma (RIF) tumor model. Assessing tumor re‐growth control across four dosimetric quantities (light fluence, photobleaching ratio, PDT dose, and [ 1 O2 ]rx ) in the RIF tumor model demonstrates that [ 1 O2 ]rx is the most reliable dosimetric metric.